Social science interdisciplinary research and challenges - Shah, Asadullah (2019)
Social science research is becoming more interdisciplinary. These research approach a problem from the perspectives of several different disciplines and where the contributions of the various disciplines are formally integrated to give a synergistic outcome where the whole is greater than the sum of the parts. While it benefits the research and body of knowledge, it also brings challenges for the researchers. This talk shed light on various types of interdisciplinary research, challenges and skills needed for an individual researcher. It also discusses the research data produced as a part of the research and the challenges associated with it. Lastly, the challenges and opportunities related to availability of the research data for others to search and use instead of reproducing the similar data are discussed.